Verification of echo amplitude envelope analysis method in skin tissues for quantitative follow-up of healing ulcers. (12th June 2018) - Omura, Masaaki; Yoshida, Kenji; Akita, Shinsuke; Yamaguchi, Tadashi
Abstract: We aim to develop an ultrasonic tissue characterization method for the follow-up of healing ulcers by diagnosing collagen fibers properties. In this paper, we demonstrated a computer simulation with simulation phantoms reflecting irregularly distributed collagen fibers to evaluate the relationship between physical properties, such as number density and periodicity, and the estimated characteristics of the echo amplitude envelope using the homodyned-K distribution. Moreover, the consistency between echo signal characteristics and the structures of ex vivo human tissues was verified from the measured data of normal skin and nonhealed ulcers. In the simulation study, speckle or coherent signal characteristics are identified as periodically or uniformly distributed collagen fibers with high number density and high periodicity. This result shows the effectiveness of the analysis using the homodyned-K distribution for tissues with complicated structures. Normal skin analysis results are characterized as including speckle or low-coherence signal components, and a nonhealed ulcer is different from normal skin with respect to the physical properties of collagen fibers.